A educação permanente e os agentes comunitários de saúde: reflexões sobre o curso introdutório para equipes de Estratégia de Saúde da Família - Soares, Maysa Rosiclécia Sousa (2016)
The present study is of an exploratory, descriptive study, with a predominantly qualitative approach. The main objective was to analyze the opinions of community health workers about the contents of the introductory level course in the city Sorocaba, identifying those not covered and those that could be added or modified. The 12 participants who agreed to share their experiences worked in teams of the Family Health Strategy. The Ethics Committee of the Medical College and Health Sciences at Pontifical Catholic University of São Paulo approved the study. Two data collection instruments were selected; structured questionnaire survey of sociodemographic characteristics of the CHA and interview script with guiding questions for the focus group technique. The treatment of sociodemographic data was used descriptive statistics and for qualitative data collected through focus group was used Bardin's content analysis. It was observed that 100% of participants were women, the majority (58.33%) aged between 31-40 years, all with education above that required by applicable legislation, 58,33% were married, with one or two children (91,67%) and service time at ESF above 5 years. All of them had long time of dwelling in the community (more than 10 years) and most (58.33%) have a family income between R$ 1,000.00 to R$ 3,000.00 equivalent to 1-3 minimum wage. As for the introductory course, the ACS revealed that it is necessary and useful, but insufficient to attend the professional needs from the complexity of the issues that arise in practice. They also reveals a huge concern with the bond presenting with the community, the difficulties arising from unplanned changes with team and finally, the course was conducted with excessive legislation and administrative contents, which actually proved to be of limited value. Understanding that the way to fill this gap is through four-way approach to training in the health field, based on teaching, management, care, and social control, a course directed to participants of the study with their own view that privileges dialogue in the process of knowledge construction by addressing problems that emerged in the focus group and are faced in everyday life